The role of human-related risk in breeding site selection by wolves. (September 2016) - Sazatornil, Víctor; Rodríguez, Alejandro; Klaczek, Michael; Ahmadi, Mohsen; Álvares, Francisco; Arthur, Stephen; Blanco, Juan Carlos; Borg, Bridget L.; Cluff, Dean; Cortés, Yolanda; García, Emilio J.; Geffen, Eli; et al.
Abstract: Large carnivores can be found in different scenarios of cohabitation with humans. Behavioral adaptations to minimize risk from humans are expected to be exacerbated where large carnivores are most vulnerable, such as at breeding sites. Using wolves as a model species, along with data from 26 study areas across the species' worldwide range, we performed a meta-analysis to assess the role of humans in breeding site selection by a large carnivore. Some of the patterns previously observed at the local scale become extrapolatable to the entire species range provided that important sources of variation are taken into account. Generally, wolves minimised the risk of exposure at breeding sites by avoiding human-made structures, selecting shelter from vegetation and avoiding agricultural lands. Our results suggest a scaled hierarchical habitat selection process across selection orders by which wolves compensate higher exposure risk to humans within their territories via a stronger selection at breeding sites. Dissimilar patterns between continents suggest that adaptations to cope with human-associated risks are modulated by the history of coexistence and persecution. Although many large carnivores persisting in human-dominated landscapes do not require large-scale habitat preservation, habitat selection at levels below occupancy and territory should be regarded in management and conservation strategies aiming to preserve these species in such contexts. In this case, we recommend providing shelter from human interference at least in small portions of land in order to fulfill the requirements of the species to locate their breeding sites. Highlights: Breeding site selection by large carnivores is driven by the risk of interaction with humans. Globally, wolves minimize the risk of exposure by avoiding manmade structures and selecting refuge-providing vegetation. Observed continental-level differences suggests wolf adaptations are modulated by the history of coexistence and persecution. Large carnivores compensate higher exposure risk at territory levels by stronger selection against it at homesites. Shelter from human interference in small portions of land will encourage large carnivore persistence.